ANALISIS KESULITAN BELAJAR SISWA PADA MUATAN PEMBELAJARAN PPKN KELAS V DI SDN KLAKAHKASIHAN 01 KECAMATAN GEMBONG KABUPATEN PATI TAHUN AJARAN 2021 - Tika Melinda; Beny Dwi Lukitoaji (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
The researcher aims to find out: (1) the factors that cause student learning difficulties in the class V Civics learning content at SDN Klakahkasihan 01, Gembong District, Pati Regency; (2) The efforts to overcome students learning difficulties in the content of Civics Class V learning at SDN Klakahkasihan 01, Gembong District, Pati Regency. This research was conducted on 5th grade students at SDN Klakahkasihan 01 in the 2021 academic year. This research is a qualitative research with descriptive analysis techniques. The subjects of this study are the homeroom teachers for grade 5 and the students of grade 5. The object of this study analyzes the factors of student learning difficulties in Civics learning content and the efforts that must be made to overcome student learning difficulties in Civics learning content. The data collection technigue of this study uses observation, interviews and documentation. Meanwhile, the data analysis uses descriptive analysis of Miles and Huberman which consists of: Data collection, data reduction, data presentation and conclusions/verification. The validity of the data uses source triangulation and technical triangulation. The findings of this study prove that students have difficulties in learning the content of Civics learning. The factors that cause students' learning difficulties in PPKn learning content are: a) Internal factors, such as student interests and talents, low student motivation, student concentration in learning that is less focused, less active in asking questions in learning activities, and low student reading activities. b) External factors, namely factors from teachers who are less than optimal in teaching, how to teach teachers, and methods used by teachers, also lack of parental supervision in home study assistance.